Risk Factors, Clinical Presentation and Parental Perception on Use of Antimicrobial Therapy for ARTI in Under 5 Children (The Planet, 2022)
Background: Acute respiratory tract infections (ARTIs) are one of the leading causes of morbidity and mortality, the most vulnerable are under 5 group. Though self-limited and mostly viral in origin unnecessary use of antibiotics for this illness has led to development of antimicrobial resistance. Methodology: This cross sectional study was conducted among 200 children aged 6 to 59 months, with symptoms of ARTI attending Pediatric OPD during 1-year study period. Data regarding sociodemographic variables of study population and respondent parent, symptoms and parental knowledge and attitude on use of antibiotic for their child’s current problem were collected. Results: In our current study we found, ARTIs, were prevalent in younger children (6 to 59 months’ group) with male predominance (62%). 82.5% children were exclusively breast fed, 90% maintained standard EPI vaccination schedule, 87.5% received vitamin A in last 6 months. Prevalence of ARTI was lower among these majority group. 48.2% respondent mother completed secondary education and monthly family income was >25,000 to 50,000 BDT in majority group (49.5%). Only 37.5% study population could afford to live in well ventilated house. Child’s age, sex and housing standard was significantly associated with development of ARTI in our study. Fever was the commonest (88%) symptom followed by runny nose (80%), cough (67.5%), wheeze (43%), dyspnea (19%), ear ache &/discharge (17.5%), sore throat (14%), chest in drawing (10%) and headache, facial pain/tenderness in (7.5%). 55% respondent parent didn’t know the etiology of pediatric ARTIs, 77% had no idea that antibiotic misuse may lead to antimicrobial resistance and 60% were unware of side effect of the drug. 32.5% parent took medicine without valid prescription from pediatrician. Conclusion: The potential risk factors of ARTI in children are preventable and modifiable. Promotion of exclusive breast feeding, vaccination, vitamin A supplementation, optimum nutrition and basic hygiene practices reduces chance of infection. Identification of the modifiable risk factors and appropriate interventions will enable to reduce the burden of this illness. Besides, provision of knowledge to general population regarding necessity of antibiotics in this illness will help to minimize misuse of this drug.
Keywords: Risk Factors; Clinical Presentation; Parental Perception; Antimicrobial Therapy; ARTI